Pengaruh Likuiditas, Leverage, Profitabilitas dan Kepemilikan Manajerial Terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Manufaktur yang Terdaftrar di BEI Tahun 2020-2022 - Agus Endro Suwarno; Izzat El-Maula Pangesti Syafi'i (Economic Reviews Journal, 2024)
A company will always strive to achieve its goals, for example long-term goals such as the ability to increase company value. Indrarini (2019: 3) defines company value as an investor's vision of the manager's success rate in managing the company's assets entrusted to him which is often associated with stock prices. The sampling technique in this study used purposive sampling method. The data collection method in the study is the annual financial report documentation method (annuar report). This study uses a type of quantitative research, the data used in the research is secondary data obtained by taking through the annual report of each manufacturing company which can be accessed through the company's official website. Liquidity has no effect on firm value, the high level of liquidity causes a decrease in firm value. Leverage affects firm value, companies with low leverage levels can increase firm value. Profitability has no effect on firm value, excessive inventory may have low profitability. Managerial ownership has no effect on firm value, the results of this study contradict agency theory.